Local Participation In Small Video Format Production For Rural Quality Of Life Improvement In Northeast Thailand: A Participatory Message Development Model Approach - Karnka, Sanun (1994)
The objectives of this study were: (1) to determine the level of local participation in small video format production for rural quality of life improvement in Northeast Thailand; (2) to examine the applicability of using small video format in participatory message development for rural quality of life improvement in Northeast Thailand; (3) To determine the factors associated with the level of local participation in small video format production for rural quality of life improvement in Northeast Thailand. A total of 176 respondents consisting of 130 learning group members ( LGMs) from four villages and forty-six nonformal educators (NFEs) from four Provincial Non-Formal Education Centres in Northeast Thailand were sampled by using